Architecture Description Approach of Information Systems to System Optimization - Cao Wei; Fan Xi-quan; Bie Xiao-wu; Liu Gang-feng; Wu Cheng-hai (Institute of Advanced Engineering and Science, 2013)
The comprehensive electronic information systems architecture is an important part of arming information-based construction, so the architecture description approach is needed to be studied with the system optimization simultaneously. In order to support system optimization, an architecture description approach of information systems is studied with the multi-perspective point’s method. Based on the data of the architecture description models, this article will analysis the data form of the description model and the logic relation of the data therefore the architecture description models can be used to optimize information systems architecture.DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2210